ESTIMATION OF AGE BY RADIOLOGICAL EXAMINATION OF FUSION OF XIPHI-STERNUM JOINT: A CROSS SECTIONAL STUDY (Journal of Forensic Medicine & Toxicology, 2025)
Introduction: Age estimation is one of the important methods of identification of a person. Determination of the age of an individual from the appearance and the fusion of the ossification centers is a well-accepted fact in the field of medical and legal professions. Method: The mean age of the male participants was 38.4 years and was 38.6 years for females. Three age groups were created (31 to 35 years, 36 to 40 years, and 41 to 45 years) Only the complete fusion of the Xiphoid process with the body of the sternum was considered as “fusion” for the present study. Result: A total of 63% of individuals showed fusion of the xiphi-sternal joint. Fusion was observed more in females (33%) as compared to males (30%). The mean age of fusion was 40.05±4.89 years in males and 40.95±3.87 years in females. The mean age of nonfusion was 35.83±3.38 years in males and 33.30±3.09 years in females. No statistically significant difference (Chi Square = 0.287 p-value = 0.592) was present in the age above which males and females show complete ossification of the xiphisternum joint.
Keywords: age estimation; dentification; sternum; xiphisternum; x-ray